Brief: Has IFPRI’s research decentralization strategy made a difference? An econometric study of African and Asian Countries, 1981–2014 - Benin, Samuel; Place, Frank; Hazell, Peter B. R. (International Food Policy Research Institute, 2018)
The International Food Policy Research Institute (IFPRI) introduced a decentralization strategy over 15 years ago that has relied heavily on outposting of staff to developing countries to work more closely with national and regional partners. This study takes an econometric approach to answering the question, “Has this strategy made a difference in terms of achieving policy and development outcomes and, if so, has this been a sound investment for IFPRI?”